Lifelong Learning in the Perspective of Hadith: Implementation and Its Relevance in Modern Life - Imam Adilan, Dilan; Mu'min, Mu'min (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This article examines the concept of lifelong learning from the perspective of hadith and its relevance to modern educational challenges. The hadith,